Step
*
1
of Lemma
bag-combine-append-right
.....equality..... 
1. A : Type
2. B : Type
3. F : A ⟶ bag(B)
4. G : A ⟶ bag(B)
5. as : A List
6. bs : A List
7. permutation(A;as;bs)
⊢ ⋃x∈as.F[x] + G[x] = (⋃x∈as.F[x] + ⋃x∈as.G[x]) ∈ bag(B)
BY
{ (ThinVar `bs'
   THEN ListInd (-1)
   THEN RepUR ``bag-combine bag-union concat bag-map bag-append`` 0
   THEN Try (Fold `concat` 0)
   THEN Folds ``empty-bag bag-union bag-map bag-append`` 0
   THEN Auto
   THEN Fold `bag-combine` 0) }
1
1. A : Type
2. B : Type
3. F : A ⟶ bag(B)
4. G : A ⟶ bag(B)
5. u : A
6. v : A List
7. ⋃x∈v.F[x] + G[x] = (⋃x∈v.F[x] + ⋃x∈v.G[x]) ∈ bag(B)
⊢ ((F[u] + G[u]) + ⋃x∈v.F[x] + G[x]) = ((F[u] + ⋃x∈v.F[x]) + G[u] + ⋃x∈v.G[x]) ∈ bag(B)
Latex:
Latex:
.....equality..... 
1.  A  :  Type
2.  B  :  Type
3.  F  :  A  {}\mrightarrow{}  bag(B)
4.  G  :  A  {}\mrightarrow{}  bag(B)
5.  as  :  A  List
6.  bs  :  A  List
7.  permutation(A;as;bs)
\mvdash{}  \mcup{}x\mmember{}as.F[x]  +  G[x]  =  (\mcup{}x\mmember{}as.F[x]  +  \mcup{}x\mmember{}as.G[x])
By
Latex:
(ThinVar  `bs'
  THEN  ListInd  (-1)
  THEN  RepUR  ``bag-combine  bag-union  concat  bag-map  bag-append``  0
  THEN  Try  (Fold  `concat`  0)
  THEN  Folds  ``empty-bag  bag-union  bag-map  bag-append``  0
  THEN  Auto
  THEN  Fold  `bag-combine`  0)
Home
Index